2019
DOI: 10.1093/ajcn/nqz100
|View full text |Cite
|
Sign up to set email alerts
|

Food neophobia associates with poorer dietary quality, metabolic risk factors, and increased disease outcome risk in population-based cohorts in a metabolomics study

Abstract: Background Food neophobia is considered a behavioral trait closely linked to adverse eating patterns and reduced dietary quality, which have been associated with increased risk of obesity and noncommunicable diseases. Objectives In a cross-sectional and prospective study, we examined how food neophobia is associated with dietary quality, health-related biomarkers, and disease outcome incidence in Finnish and Estonian adult po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 49 publications
1
32
0
5
Order By: Relevance
“…Despite the fact, that CD-FAB is brief, self-report questionnaire that shows good reliability and validity in measuring disordered eating attitudes and behaviors in CD patients, it covers a lot of themes exploring food attitudes, concerns, and eating behaviors (i.e., handling of food, trust, risk-taking, and food safety), whereas the FNS is focused only on one narrow aspect. The CD-FAB could measure the relationship between attitudes, concerns, and eating behaviors and quality of life, but it was observed that total CD-FAB is positively correlated with the FNS [24]. The FNS is, at the same time, closely linked to adverse eating patterns and reduced dietary quality, which is related to an increased risk of obesity and non-communicable diseases which was proven in the recent study of Sarin et al [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact, that CD-FAB is brief, self-report questionnaire that shows good reliability and validity in measuring disordered eating attitudes and behaviors in CD patients, it covers a lot of themes exploring food attitudes, concerns, and eating behaviors (i.e., handling of food, trust, risk-taking, and food safety), whereas the FNS is focused only on one narrow aspect. The CD-FAB could measure the relationship between attitudes, concerns, and eating behaviors and quality of life, but it was observed that total CD-FAB is positively correlated with the FNS [24]. The FNS is, at the same time, closely linked to adverse eating patterns and reduced dietary quality, which is related to an increased risk of obesity and non-communicable diseases which was proven in the recent study of Sarin et al [24].…”
Section: Discussionmentioning
confidence: 99%
“…It must be mentioned that individuals with food neophobia may reduce the consumption of some health-promoting products [23], and as a result, it may be associated with an increased risk of obesity and non-communicable diseases [24]. Taking this into account, it must be emphasized that knowledge about food neophobia in patients following an elimination diet would allow to properly formulate the dietary recommendations for them.…”
Section: Introductionmentioning
confidence: 99%
“…For example, food neophobia is negatively associated to daily intake and liking of fruit and vegetables [ 18 , 19 ] as well as of food of animal origin, especially fish [ 20 ]. Recent evidence has shown that the effect of food neophobia may extend beyond rejection of unfamiliar/unusual foods to encompass many commonplace food items [ 21 , 22 ], reducing the nutritional quality of an overall diet and increasing metabolic disease risk [ 23 ] and obesity [ 24 ]. For instance, Sarin and co-workers [ 23 ] have recently demonstrated in a large population cohort of Finnish and Estonian adults that food neophobics have lower scores of a healthy Nordic diet and a higher incidence of coronary heart disease and type 2 diabetes, as assessed by health-related biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Food neophobia is a heritable trait by up to 78% [ 25 ]. This behavioral trait is especially evident during childhood as a developmentally appropriate response against the ingestion of new and potentially toxic foods [ 23 ]; however, food neophobia has a high prevalence also among adults [ 21 , 22 , 26 , 27 ], and its association with individual factors, such as age, gender, personality features, living area, education level, and socioeconomic status, has been reported [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the increase in neophobia may lead to the consumption of more energy dense foods with poor nutritional composition. Therefore, it is essential to find means to introduce healthy and nutritious foods to fight overweight and obesity to promote child’s health without triggering a neophobic response [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%